Population, Nest Distribution, and Nest Characteristics of Great Egret in Pulau Rambut Wildlife Sanctuary, Jakarta Bay - Sekar Wilis Sudarsono; Ani Mardiastuti; Yeni Aryati Mulyani (Institut Pertanian Bogor, 2026)
Pulau Rambut, a 45-hectare island in Jakarta Bay, is a major nesting and roosting location for waterbirds, especially the great egret (Ardea alba). This species has faced population constraints due to habitat loss, oil spills, and waste. Bio-ecological data on this species has been lacking. The purpose of this study was to quantify population size, analyze nest tree distribution, investigate nesting associations, and describe nest and egg features during the peak breeding season (March–April 2025). The birds were counted in the morning when they flew away and, in the evening, when they returned to the island. Nest trees were mapped, and nest tree attributes were assessed on trees discovered throughout the search. Field observations revealed an estimated 135 great egrets, mostly on the island's eastern side. Nests were mostly found in the uppermost canopy of Rhizophora mucronata (average height 13.8±2.3 m; diameter 20.0±7.1 cm; n = 19) and Rhizophora stylosa. Nests were cup-shaped, twig-based constructions measuring 46.8×38.5 cm with a depth of 42.3 mm. Purple herons (Ardea purpurea) were regularly observed to nest together. The clutch size averaged 2.2 eggs per nest (range: 1−4; mode: 2). The eggs were oval, pale blue-green, and averaged 50.9×35.8 mm in size, weighing 35.9±6.3 g (n = 19). These data represent the first thorough bio-ecological baseline for great egrets on Pulau Rambut. Conservation and restoration of mangrove ecosystems, particularly R. mucronata, is critical for sustaining great egret breeding numbers and minimizing future population decreases in the sanctuary. Keywords: Ardea alba, nest characteristics, Rhizophora mucronata, waterbird